2000
DOI: 10.1080/028418500127346090
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of anterior dislocation of the shoulder

Abstract: Anterior dislocations of the shoulder require different methods of reduction depending upon the type (sub-group) of dislocation. Reduction of subglenoid dislocations with associated greater tuberosity fracture should be performed under general anesthesia to avoid head-splitting fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A fall on to the outstretched arm transmitting the force to the glenohumeral joint is a typical mechanism. The vast majority of dislocations are anterior (97%) and the remaining and posterior (Ceroni et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A fall on to the outstretched arm transmitting the force to the glenohumeral joint is a typical mechanism. The vast majority of dislocations are anterior (97%) and the remaining and posterior (Ceroni et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In general, GHJ dislocation occurs due to a fall on the arm, specific set of stresses on the arm, axial load on the arm, or a direct blow to the shoulder. Anterior GHJ dislocation is usually due to a combination of forcible abduction, extension, and external rotation of the arm (1,(4)(5)(6). Rarely, anterior GHJ dislocation results from a direct blow to the posterior shoulder (4).…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Studies suggest that the majority of anterior GHJ dislocations are of the subcoracoid (Fig. 5) subtype (about 66% to 75%), while the subglenoid subtype occurs 25% to 33% of the time (4,5,14,15). Subglenoid subtypes should not be confused with true inferior dislocations (luxatio erecta).…”
Section: Current Classificationmentioning
confidence: 99%
“…It is reported that up to 25% of these injuries are fracture-dislocations. [1,2] While isolated dislocations can be Cite this article as: Durak VA, Atıcı T. Diagnostic accuracy of Fresno-Quebec Rules and risk factors for an associated fracture in patients presenting to the emergency department with anterior shoulder dislocation: A retrospective study. Ulus Travma Acil Cerrahi Derg 2020;26:115-121.…”
Section: Introductionmentioning
confidence: 99%